PELATIHAN PENINGKATAN KAPASITAS MASYARAKAT DALAM USAHA PERLINDUNGAN DAN PENGELOLAAN EKOSISTEM DALAM PENGEMBANGAN GILI SEJANGAN SEBAGAI EKOWISATA DI DESA LABUHAN KURIS KECAMATAN LAPE - Lahmuddin Zuhri; Iwan Haryanto; Zuama Widyaiswara; Sri Fitriani (FKIP Universitas Samawa, 2021)
Community capacity-building activities are aimed at increasing community knowledge and understanding in the protection and management of ecosystems in the development of Gili Sejangan as ecotourism in Labuhan Kuris Village, Lape District. The methods used are based on potential and problems, counseling, discussion and question, and answer, as well as monitoring and evaluation. The results obtained from the training were almost all of the community or participants who had knowledge and understanding regarding the protection of mangrove forests and coral reefs, management in managing fish products that can be sold in shops, managing Gili Senjangan as ecotourism, and utilizing the waters as a place for fish cultivation. using modern floating cages.